Efficiency of repeated corrective surgeries in patients with spinal defor- mities: analysis of the immediate results of a monocenter cohort and a brief review of the literature - Mikhail V. Mikhaylovskiy; Artem N. Sorokin; Aleksandr Yu. Sergunin; Elena V. Gubina (Хирургия позвоночника, 2023)
Objective. To analyze the results of repeated corrective surgery in patients with spinal deformities of various etiologies. Material and Methods. The study group included 87 patients (mean age is 22.8 years, m : f = 10 : 77) who underwent repeated deformity correction using third-generation instrumentation (CDI and its analogues), and were selected from 144 patients previously operated on for spinal deformities of various etiologies using different types of spinal instrumentation. The magnitude of scoliotic deformity, thoracic kyphosis, lumbar lordosis, rotation of the apical vertebra, the volume of intraoperative blood loss, and the duration of the operation were assessed. All patients answered the questions of the SRS-24 questionnaire at the stages of treatment and postoperative follow-up, and were also examined by computer optical topography method. Results. Out of 87 reoperated patients, 74 had idiopathic scoliosis. In 31 patients, the results were evaluated within a period of at least 2 years (average 61.8 months). As a result of the intervention, the primary curve was corrected by 29.1° (36.5 %). Loss of correction was 4.6° (p < 0.001), derotation of the apical vertebra – from 34.9° to 22.1° (p < 0.001) and loss of correction – 0.8°. The average blood loss varied from 810 to 1138 ml, and the operation time – from 187 to 289 min. Computer optical topography data convincingly confirmed the corrective effect achieved during the repeated intervention. According to the questionnaire (SRS-24), satisfaction with the results of the operation was quite high. Conclusion. Repeated corrective interventions in patients with spinal deformities of various etiologies, even in long-term periods, can partially restore the lost primary correction and improve the quality of life of patients, which is confirmed by clinical and radiographic data, the results of computer optical topography and the SRS-24 questionnaire.